Nuclide Identification using CsI(Tl) Gamma Ray Spectra and Neural Networks - Maiwald, Timo; Leder, Erich; Pijahn, Ralf; Buchhold, Reinhard; Fischer, Georg (21st IEEE International Conference on Machine Learning and Applications (ICMLA), 2023)
With increasing popularity of machine learning methods used in gamma ray spectroscopy for radioisotope identification, quality and scope of the data, to train and evaluate models, constitute the key towards applicable approaches. This paper demonstrates several steps needed to be considered in order to create a novel dataset, which is motivated by physical, technical and standardization requirements. Therefore offset shifts, gain drifts, variating acquisition times and nuclide mixtures are considered. Furthermore, initial classification results gained from a neural network approach are presented.<br
Keywords: nuclide identification; gamma ray spectra; machine learning; neural networks